Effects of Ocimum basilicum Linn Essential Oil and Sodium Hexametaphosphate on the Shelf Life of Fresh Chicken Sausage - Barbosa, Lidiane Nunes [UNESP]; Bergamo Alves, Fernanda Cristina [UNESP]; Murbach Teles Andrade, Bruna Fernanda [UNESP]; Albano, Mariana [UNESP]; Castilho, Ivana Giovannetti [UNESP]; Mores Rall, Vera Lucia [UNESP]; Athayde, Natalia Bortoleto [UNESP]; Casagrande Delbem, Nara Laiane [UNESP]; Roca, Roberto de Oliveira [UNESP]; Fernandes Junior, Ary [UNESP] (Int Assoc Food Protection, 2014)
Although consumers and the food industry have an interest in reducing the use of synthetic additives, the consumption of processed meat in Brazil has been increasing because of the easy preparation and low cost. Owing to the antimicrobial and antioxidative properties of Ocimum basilicum essential oil (EO), it has potential applications in food products. Polyphosphates are already used in meat processing with the goal of improving the quality of the products. The aim of this work was to assess the effects of sodium hexametaphosphate (SHMP) and O. basilicum EO, when added separately or together, on physical, chemical, and microbiological parameters during the shelf life of chicken sausage. We also performed sensory analysis of the product prepared in this manner. Six different treatments were produced in which the substances were tested together or separately, and the content of EO was 0.3 or 0.03%. The samples were analyzed after 1, 7, and 15 days of storage at 4 degrees C. An increase in pH on days 7 and 15 in samples that contained SHMP was observed. In the samples that contained either 0.3 or 0.03% EO, coliforms were inhibited throughout the study period (P < 0.05), which was not observed in samples with EO plus SHMP, thus demonstrating that the stabilizer blocked the antibacterial action of EO. There was a reduction in the cook loss and increased compressive force in the samples with 0.5% SHMP, contributing to greater juiciness of the product. The EO had substantial impact on acceptability of samples, but it did not influence the activities already described of polyphosphate.